2001
DOI: 10.1590/s0004-28032001000400006
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Helicobacter pylori in gastric cancer

Abstract: -Background and Objectives -Considering the high prevalence of stomach cancer in the northern region of Brazil and the recognized relationship between chronic gastric inflammation caused by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
8
2
Order By: Relevance
“…In the diffuse-type carcinoma the H. pylori was predominantly negative when the Giemsa and urease test were used. Our results are in contradiction to the works published by other authors (6,35) . H. pylori infection was found in 63.6% of patients with intestinal type early gastric cancer and in 54.5% of patients with diffuse-type early gastric cancer (9) .…”
Section: Discussioncontrasting
confidence: 99%
“…In the diffuse-type carcinoma the H. pylori was predominantly negative when the Giemsa and urease test were used. Our results are in contradiction to the works published by other authors (6,35) . H. pylori infection was found in 63.6% of patients with intestinal type early gastric cancer and in 54.5% of patients with diffuse-type early gastric cancer (9) .…”
Section: Discussioncontrasting
confidence: 99%
“…This finding might be explained by the etiopathogenesis of gastric adenocarcinoma of the intestinal type, which is characterized by atrophic gastritis and intestinal metaplasia and involves factors such as dietary habits, exposure to H. pylori and smoking that share the preference for distal portions of the stomach (5,13,14,19,36) . Other studies have demonstrated the participation of these factors in the etiopathogenesis of gastric adenocarcinoma in the State of Pará (9,25,27,28,37) . Macroscopic analysis showed that most cases were advanced tumors, with the observation of a larger number of ulcerated-infiltrative lesions (Borrmann III), followed by ulcerated and delimited lesions (Borrmann II).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, studies have shown a high prevalence of infection with Helicobacter pylori among patients with gastric adenocarcinoma from the State of Pará (25,37) . Taken together, these factors may explain the high incidence of gastric cancer in this region.…”
Section: Case Study Of Stomach Adenocarcinoma Conducted At a Cancer Rmentioning
confidence: 99%
“…In this study, we used the modified Gram staining method because it is widely utilised (Araujo et al 1993, Pereira et al 2001, Assumpção et al 2010 for the detection of bacteria in humans and has also been employed in studies with monkeys (Mackie & O'Rourke 2003).…”
Section: Discussionmentioning
confidence: 99%